THE PLACE OF ARABIC IN THE CONDUCT OF WOMEN TAFSIR IN JOS METROPOLIS, NIGERIA - Sani, Fatima Muhammad; Yahaya, Atiku Garba (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2023)
This research titled ‘The Place of Arabic in the conduct of Women Tafsir in Jos Metropolis’, discusses Arabic as language of Qur’an, Brief overview of the development of Tafsir and women Tafsir in Jos metropolis in relation to certain circles where women attain to the teaching and interpretations of the Glorious Qur’an. The research applies qualitative designed and employs the methods of sampling and interview using purposive sampling. The research selected six different Tafsir circles in Jos metropolis. It is discovered that most of the women Tafsir in the various circles are conducted by Muslim Male scholars of Islamic knowledge and those having higher qualifications in Arabic studies, using different Arabic books of Tafsir. Some of the Tafsir circles have been in existence for some years, there are few that are new. It has been discovered that most of the places where women attain Tafsir in Jos are self-funded, with inadequate equipment and lack of funds.